The cholinergic anti-inflammatory pathway inhibits inflammation without lymphocyte relay - Simon, Thomas; Kirk, Joseph; Dolezalova, Nikola; Guyot, Mélanie; Panzolini, Clara; Bondue, Alexandre; Lavergne, Julien; Hugues, Sandrine; Hypolite, Nicolas; Saeb-Parsy, Kourosh; Perkins, Justin; Macia, Eric; et al. (Frontiers in Neuroscience, 2023)
The magnitude of innate inflammatory immune responses is dependent on interactions between peripheral neural and immune cells. In particular, a cholinergic anti-inflammatory pathway (CAP) has been identified in the spleen whereby noradrenaline (NA) released by splenic nerves binds to ß2-adrenergic receptors (β2-AR) on CD4+ T cells which, in turn, release acetylcholine (ACh). The binding of ACh to α7 acetylcholine receptors (α7-AChR) expressed by splenic macrophages inhibits the production of inflammatory cytokines, including tumor necrosis factor (TNF). However, the role of ACh-secreting CD4+ T-cells in the CAP is still controversial and largely based on the absence of this anti-inflammatory pathway in mice lacking T-cells (nude, FoxN1−/−). Using four conscious, non-lymphopenic transgenic mouse models, we found that, rather than acting on CD4+ T-cells, NA released by splenic nerve terminals acts directly onto β2-AR on splenic myeloid cells to exert this anti-inflammatory effect. We also show that, while larger doses of LPS are needed to trigger CAP in nude mouse strain compared to other strains, TNF production can be inhibited in these animals lacking CD4+ T-cell by stimulating either the vagus or the splenic nerve. We demonstrate that CD4+ T-cells are dispensable for the CAP after antibody-mediated CD4+ T-cell depletion in wild type mice. Furthermore, we found that NA-mediated inhibition of in vitro LPS-induced TNF secretion by human or porcine splenocytes does not require α7-AChR signaling. Altogether our data demonstrate that activation of the CAP by stimulation of vagus or splenic nerves in mice is mainly mediated by direct binding of NA to β2-AR on splenic macrophages, and suggest that the same mechanism is at play in larger species.